KEDUDUKAN KOPERASI YANG DINYATAKAN PAILIT DALAM PERMOHONAN PEMBAYARAN HUTANG - VETRA R. BERKATSYAH SINAGA (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Sunarmi2. Budiman Ginting3. Muhd Yamin A cooperative suffers a loss and is not able to pay off its debt, two methods can be used to solve the problem, either by the decision of membership meeting or by the government directive. The Ruling No. 01/Pailit/2008/PN.Niaga.Smg states the bankruptcy of Koperasi SAM, located in Solo, by the request for bankruptcy by its three managers: BS, LTT, and AW. This research was descriptive analytic with judicial normative approach. The data comprised secondary data which were obtained by gathering primary, secondary, and tertiary legal materials. The legal consequence of the ruling on the bankruptcy of the cooperative’s assets was that all of the cooperative’s assets were under the curators’ control and management. Generally, the rest of the assets of a cooperative which has been closed down is not sufficient to pay off the debt. The legal status of a cooperative as the result of bankruptcy is that it will be closed down. The problems usually come from the debtors who have bad intention or who do not want to pay off their debts; they can embezzle investment when the curators are filing the debtors’ assets by transferring their assets to other places. The result is that the curators cannot detect the debtors’ assets. The non-professional curators in managing bankrupted debtors’ assets can cause another problem. When a cooperative is closed down, its members are only responsible for their main savings and initial capital they have deposited. In the case of some members who give their personal loan to the cooperative, they will have the same status as the other creditors in claiming the payoff of the loan to the cooperative which has a legal entity.Keywords: Status of Cooperative, Bankruptcy, Request for Paying Off Debt